Plasma membrane-targeted ras GTPase-activating protein is a potent suppressor of p21ras function. - Huang, D C (1993)
Although p21ras is localized to the plasma membrane, proteins it interacts with, such as the GTPase-activating proteins (GAPs) ras GAP and neurofibromin (NF1), are not, suggesting that one function of p21ras GTP may be to target such proteins to the plasma membrane. To investigate the effects of targeting ras GAP to the plasma membrane, ras C-terminal motifs sufficient for plasma membrane localization of p21ras were cloned onto the C terminus of ras GAP. Plasma membrane-targeted ras GAP is growth inhibitory to NIH 3T3 fibroblasts and COS cells. This growth inhibition correlates with GAP catalytic activity, since the plasma membrane-targeted C-terminal catalytic domain or the GAP-related domain of neurofibromin is inhibitory, whereas the similarly targeted N-terminal domain is not. Moreover, the inhibition is abrogated by the inactivating mutation L902I, which abolishes ras GAP catalytic activity. Coexpression of oncogenic mutant ras rescues cell viability, but the majority of rescued colonies are phenotypically untransformed. Furthermore, in focus assays, targeted ras GAP suppresses transformation by oncogenic mutant ras, and in reversion assays, targeted ras GAP can revert cells transformed by oncogenic mutant ras. Neither the targeted or nontargeted N-terminal domain nor the L902I mutant of ras GAP has any transforming activity. These data demonstrate that ras GAP can function as a negative regulator of ras and that plasma membrane localization potentiates this activity. However, if ras GAP is involved in the effector functions of p21ras, it can only be part of the effector complex for cell transformation.